Effect of natural gas composition and gas interchangeability on performance and emission characteristics in an air–fuel controlled natural gas engine. (1st March 2021) - Park, Cheolwoong; Oh, Sechul; Kim, Changgi; Choi, Young; Ha, Youngcheol
Highlights: HHV, WI and MCP are not suitable as an interchangeability index of engine. Engine performance is most closely related to the gas combustion rate. The combustion rate of pure methane is slowest among low calorific gases. The MCP value is calculated by excessively reflecting the influence of the inert gas. Modified MCP is a suitable interchangeability index of an air–fuel controlled engine. Abstract: In this study, the effect of low-calorie gas on the output performance and efficiency of engines and the emission characteristics was investigated using an 11 L 6-cylinder supercharged engine for city buses. In order to examine the effect of changes in the physical properties of low calorific gas on combustion, the results with simulated low calorific natural gas by the addition of nitrogen were compared to those with reference natural gas fuel. Pure methane (CH4 ) is also used to investigate the effect of gas composition change on the performance and emission characteristics. The basic performance factors, including torque and thermal efficiency, were compared by varying the engine speed under full-load operating conditions. The trends of exhaust gas emissions were observed and analyzed with respect to the fuel composition. Another purpose of this study is to determine whether the higher heating value (HHV), Wobbe index (WI), and maximum combustion potential (MCP) index are appropriate factors for determining the performance and exhaust condition of the air–fuel controlled engine for the composition of the gas used in this study. It was found that the combustion rate is the most important physical property of the gas, while the MCP does not match the laminar flame speed of low calorific gas fuel and pure CH4 . The modified MCP value is presented and is a suitable gas interchangeability index of the engine that controls the air–fuel ratio because it properly reflects the effect of the inert gas in the fuel gas.